(untitled) (Baghdad Science Journal, 2017)
The present work included qualitative study of epiphytic algae on dead and living stems, leaves of the aquatic plant Phragmitesaustralis Trin ex Stand, in Tigris River in AL- Jadria Site in Baghdad during Autumn 2014, Winter 2015, Spring 2015, and Summer 2015. The physical and chemical parameters of River’s water were studied (water temperature, pH, electric conductivity, Salinity, TSS, TDS, turbidity, light intensity, dissolve oxygen, BOD5, alkalinity, total hardness, calcium, magnesium and plant nutrient). A total of 142 isolates of epiphytic algae were identified. Diatoms were dominant by 117 isolates followed by Cyanobacteria (13isolates), Chlorophyta (11 isolates) and Rhodophyta (1 isolate), Variations in the isolates number were recorded on different parts of macrophyte host as well as, indifferent seasons. Eight new algal isolates (Achnanthesexigue var. heterovalvata Krasske, Navicula exilissima Grunow, Navicula falaisiensis var lanceola Grunow, Navicula microcephalo Grunow, Pleurosigma obscurum W. Smith, Stauroneis amphioxys var. amphioxys Gregory, Stenopterobia intermedia Lewis and Audouinella hermannii Roth).were identified as new records.